Chondrocranium and cranial muscle morphology in Lysapsus and Pseudis tadpoles (Anura: Hylidae: Hylinae) - Alcalde, Leandro (2006)
The chondrocranium and cranial muscles of Lysapsus limellum, Pseudis cardosoi, P. minuta and four subspecies of P. paradoxa (caribensis, occidentalis, paradoxa and platensis) are described. Lysapsus and Pseudis are related to the Hylidae by: (1) vertical processus anterolateralis of the larval crista parotica, and (2) presence of m. mandibulolabialis inferior and superior (the latter reversed in P. cardosoi). We confirm some larval synapomorphies previously proposed for the pseudids, except the m. subarcualis obliquus II having one head and the absence of copula anterior. We add three new features for the pseudids: (1) the distal end of ceratobranchiales III and IV projects towards either the capsula auditiva (Lysapsus) or the processus basicapsularis – new term – (Pseudis); (2) the arcus subocularis is twice as wide at the level of the processus ascendens as it is just posterior to the processus muscularis quadrati, and (3) the lateral corner of the processus articularis quadrati largely projects laterally. We diagnose Lysapsus larvae (the states of Pseudis in parentheses) as follows: (1) short processus pseudopterygoideus (long), (2) absence of lateral development of larval crista parotica (presence), (3) absence of commissura proximalis II (presence), (4) presence of processus lateralis hyalis – new term – (absence), (5) absence of processus basicapsularis (presence), (6) processus ascendens slightly curved along its entire extent (curved at the union with the basi cranii only), and (7) absence of m. tympanopharyngeus (presence).